Perencanaan dan Implementasi Optical Distribution Point Dua Kompartemen Untuk Meningkatkan Performansi Jaringan Fiber Optik - Kardiyasa, Komang Agus Putra; Gunantara, Nyoman; Sudarma, Made (Majalah Ilmiah Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2024)
This research addresses challenges in the Optical Distribution Point (ODP) in fiber optic networks, starting with identifying issues affecting network performance. The study emphasizes the importance of reliable ODPs in enhancing overall network efficiency. Through careful planning and evaluation, this research focuses on designing a two-compartment ODP system. The research findings highlight that robust ODPs positively impact network performance by improving signal quality, transmission speed, and overall reliability. The study also explores the economic feasibility of implementing this system, ensuring that the proposed ODP solution is not only technically superior but also cost-effective based on feedback from 360 respondents, stating that the 2-Compartment ODP device can reduce operational costs and network infrastructure maintenance. This research provides valuable insights into the field of optical fiber communication, laying the groundwork for future advancements in network planning and infrastructure, ultimately aiming to optimize the performance of fiber optic access networks.